2022
DOI: 10.3389/fnut.2022.1032289
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the production of a selenium-enriched polysaccharide from Cordyceps cicadae S1 and its structure and antioxidant activity

Abstract: The fermentation medium of a newly identified Cordyceps cicadae S1 was optimized by response surface methodology, with the optimal medium containing sucrose (80 g/L), yeast powder (60 g/L), KH2PO4 (5 g/L), MgSO4·7H2O (1 g/L) and Na2SeO3 (0. 1 g/L). Under these conditions, the extracellular polysaccharide yield was 8.09 g/L. A novel selenium-enriched polysaccharide (PACI-1) was isolated from Cordyceps cicadae, purified and identified as a homofructose polysaccharide with a low average molecular weight of 9.95 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Therefore, finding a supplement with antioxidant properties is a vital goal in slowing down the development of cataracts. C. cicadae has been reported to contain antioxidant and anti-inflammatory effects in several previous study [ 30 , 32 , 38 , 39 ]. Moreover, a clinical study found C. cicadae can ameliorate dry eye symptoms [ 29 ], demonstrating that the potential of using C. cicadae in eye diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, finding a supplement with antioxidant properties is a vital goal in slowing down the development of cataracts. C. cicadae has been reported to contain antioxidant and anti-inflammatory effects in several previous study [ 30 , 32 , 38 , 39 ]. Moreover, a clinical study found C. cicadae can ameliorate dry eye symptoms [ 29 ], demonstrating that the potential of using C. cicadae in eye diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of PGPs was observed by scanning electron microscope (SEM). A total of 1 µg/mL PGPs-water solution was dropped on a clean and flat mica substrate, naturally air-dried and observed using an atomic force microscope equipped with a silicon SPM probe (AFM; Nanosurf, CH) (14).…”
Section: Characterization Of Pgpsmentioning
confidence: 99%
“…In this study, two types of column chromatography elution methods were applied, and the water-soluble component was loaded on Sephacryl S200 HR column (2.6 × 90 cm) with 0.2 mol/L NH 4 HCO 3 as eluent to obtain the monomer polysaccharide. Zhuansun et al [65] used the traditional DEAE-52 column combined with Sephadex G-100 column to obtain an extracellular homopolysaccharide from fermentation medium of Cordyceps cicadae. Furthermore, Tang et al [66] obtained a novel polysaccharide from Cordyceps cicadae, named JCH-a1, which was extracted by ultrasonically assisted enzymatic extraction and purified with cellulose DEAE-32 and Sephadex G-100 column chromatography.…”
Section: Purification and Isolation Of Polysaccharides From Fungal Tcmmentioning
confidence: 99%
“…And it was dominantly composed of mannose, glucose and galactose in a molar ratio of 10.6:1.0:3.7 [39]. Wanwan et al [65] purified a homopolysaccharide (PACI-1), which composed of fructose, and the NMR spectrum showed that PACI-1 mainly contained β-configured pyranoside bonds. Unfortunately, the methylation analysis is deficient in this study, so the specific chemical structure of PACI-1 still remains unknown.…”
Section: Cordycepsmentioning
confidence: 99%